British Association of Urological Surgeons (BAUS) consensus document: management of bladder and ureteric injury. (7th May 2021) - Sahai, Arun; Ali, Ased; Barratt, Rachel; Belal, Mohammed; Biers, Suzanne; Hamid, Rizwan; Harding, Christopher; Parkinson, Richard; Reid, Sheilagh; Thiruchelvam, Nikesh; ,
Abstract : Injuries to the bladder and ureter are uncommon but usually require prompt urological management. Due to their infrequent nature, Urologists maybe unfamiliar with managing these acute problems and may not work in specialist centres with readily available expertise in open and abdominal surgery. We aim to provide advice in the form of a consensus statement led by the Female, Neurological and Urodynamic Urology (FNUU) Section of the British Association of Urological Surgeons (BAUS), in consultation with BAUS members and consultants working in units throughout the UK, to create a comprehensive management pathway and a series of statements to aid clinicians.